Improving Students’ Mathematics Learning Achievement Through a Culturally Responsive Teaching Approach Supported by Spinner Media - Lasmiasih; Wanda Nugroho Yanuarto; Purwani (Universitas Tidar, 2025)
This study aims to improve the mathematics learning achievement of third-grade students at a public elementary school in Central Java, particularly on the topic of presenting data in tabular form, through the implementation of the Culturally Responsive Teaching (CRT) approach supported by a spinner media. The problem addressed in this study is the low level of students’ mathematics achievement, which was below the Minimum Mastery Criteria. This study employed a Classroom Action Research design using the Kemmis and McTaggart spiral model, consisting of planning, action, observation, and reflection stages. The results demonstrated a consistent improvement in learning achievement in each cycle. In the pre-cycle phase, the students’ average score was 65. In Cycle I, the classical mastery percentage reached 35% with an average score of 67. A significant improvement was observed in Cycle II, where the mastery percentage increased to 91% with an average score of 89. These findings indicate that the implementation of the Culturally Responsive Teaching approach, supported by spinner media, was effective in improving the mathematics learning achievement of third-grade students at the school.